A high-voltage non-aqueous hybrid supercapacitor based on the N2200 polymer supported over multiwalled carbon nanotubes. Issue 28 (13th July 2021) - Wavhal, Bhaiyyasaheb Anurath; Ghosh, Meena; Sharma, Sandeep; Kurungot, Sreekumar; SK, Asha
Abstract : An N2200/MWCNT composite showing a battery-type electrochemical signature performs as an efficient negative electrode in a high-voltage (2.4 V) hybrid supercapacitor comprising activated carbon as a positive electrode. Abstract : P(NDI2OD-T2), also known as Polyera ActivInk N2200, is a widely accepted non-fullerene acceptor polymer that is used prominently in the energy harvesting application due to its ease of synthesis, high electron mobility, and other desirable semiconducting properties. With its recent foray into energy storage applications, there is tremendous potential for developing composites of N2200 with carbon nanotubes (CNTs) to improve its electrical properties and extend its applicability. Here we report a facile synthesis of an N2200 composite with multiwalled carbon nanotubes (MWCNTs) following an in situ approach to include MWCNTs into the polymer matrix, improving its electrochemical performance in an organic electrolyte (1 M LiClO4 /propylene carbonate). The composite material with an optimum MWCNT content exhibits prominent redox behavior delivering a specific capacity of 80 mA h g −1 (polymer) in a standard three-electrode cell. Moreover, the N2200/MWCNT composite material showing a battery-type electrochemical signature could perform as an efficient negative electrode in a high-voltage (2.4 V) hybrid supercapacitor device comprising capacitive activated carbon as the positive electrode.